Co-administration of adjuvants along with Moringa oleifera attenuates beryllium-induced oxidative stress and histopathological alterations in rats. (October 2015) - Agrawal, Narottam Das; Nirala, Satendra Kumar; Shukla, Sangeeta; Mathur, Ramesh
Abstract Context: Moringa oleifera Lam. (Moringaceae) is a rich source of antioxidants. All parts of the plant are medicinally important and have been used as traditional medicine for a variety of human ailments in India. Objective: Therapeutic efficacy of adjuvants with M. oleifera (MO) root extract was investigated against beryllium-induced oxidative stress. Materials and methods: Hydroalcoholic (50% v/v) root extract of M. oleifera (150 mg/kg, p.o.) alone and combinations of M. oleifera with either piperine (2.5 mg/kg, p.o.) or curcumin (5.0 mg/kg, p.o.) daily for 1 week were administered in experimental rats against beryllium toxicity (1.0 mg/kg, i.p. daily for 5 weeks). Oxidative stress parameters including blood sugar, G-6-Pase in liver, and DNA damage were analyzed. Histopathological changes in liver and kidney were also observed. Results: Beryllium enhanced lipid peroxidation (LPO), depleted reduced glutathione (GSH) and antioxidant enzymes activities, decreased blood sugar and G-6-Pase activity, and did not damage DNA. Histologically, liver was observed with structural loss and disintegration of hepatocytes, heavy vacuolation in hepatocytes, and kidney was observed with constriction of glomeruli and hypertrophy in epithelial cells of uriniferous tubules. Therapy of M. oleifera with piperine was effective; however, combination of M. oleifera with curcumin showed better therapeutic effect by reduction of LPO, elevated GSH level, maintained antioxidant enzymes activities, restored blood sugar, and G-6-Pase activity in liver together with almost normal histoarchitecture of liver and kidney. Discussion and conclusion: Curcumin enhanced therapeutic efficacy of M. oleifera root extract and showed better antioxidant potential against beryllium toxicity.